Who has never tested for HIV following a community-based distribution of HIV self-test kits? Establishing associated predictors in rural Zimbabwe. - Wellington Murenjekwa; Kudzai Chidhanguro; Frances M Cowan; Fiona C Lampe; Cheryl Johnson; Amon Mpofu; Getrude Ncube; Owen Mugurungi; Karin Hatzold; Elizabeth L Corbett; Andrew N Phillips; Euphemia Sibanda; et al. (PLOS Global Public Health)
In 2023, Zimbabwe attained the 95-95-95 UNAIDS targets. However, some sub-populations are substantially less likely to have tested for HIV. Knowledge of characteristics of these groups is crucial in designing interventions that address their needs. We estimated the prevalence and predictors of "never-having tested for HIV" status following community-based distribution of HIV self-test kits in rural Zimbabwe. We analysed data from a household survey conducted as part of a cluster randomised trial comparing two community-based HIVST distribution models in six rural districts in 2018-19. HIVST distribution was conducted over one month, followed by the household survey after four months. Survey participants aged 16 years and above completed self-administered Audio-Computer-Assisted-Survey-Instrument. Unadjusted and adjusted mixed effect logistic regression was used to identify factors associated with never-having-tested for HIV. Of the 11,076 analysed participants, the median (IQR) age was 32(22,45) years and 54.5% were female. Seventeen percent of participants had never tested for HIV, primarily due to a perceived lack of HIV risk (50%). Never testers were more likely to be: men (adjusted odds ratio [AOR]=1.69;95%Confidence Interval [CI]=1.52-1.87); younger (16-24 years (AOR=3.84; 95%CI=3.23-4.55), 25-34 years (AOR=1.30; 95%CI=1.07-1.59)) and at-least 45 years old: (AOR=2.17; 95%CI=1.80-2.60); having lower levels of education: primary/less (AOR=1.68; 95%CI=1.46-1.98), some secondary (AOR=1.62; 95%CI=1.42-1.86) compared to at least complete secondary, unemployed (AOR=1.39; 95%CI=1.15-1.69); never married (AOR=3.48; 95%CI=2.98-4.07) and previously married (AOR=1.41; 95%CI=1.19-1.68) compared to currently married; having stigmatizing beliefs (AOR=1.42; 95%CI=1.24-1.62); having: low (AOR=1.52, 95%CI=1.32-1.74) and medium (OR=1.53, 95%CI=1.33-1.75) levels of treatment optimism; not participating in household decisions (AOR=1.96; 95%CI=1.70-2.27) and not reporting condomless sex (AOR=2.58; 95%CI=2.31-2.87). The Ministry of Health need to scale up acceptable and targeted interventions to improve HIV testing in different subpopulations which includes but not limited to young people, unmarried, unemployed, those with stigmatizing beliefs and those not participating in decision making.